Impaired left ventricular global longitudinal strain in patients with heart failure with preserved ejection fraction: insights from the RELAX trial. (14th February 2017) - DeVore, Adam D.; McNulty, Steven; Alenezi, Fawaz; Ersboll, Mads; Vader, Justin M.; Oh, Jae K.; Lin, Grace; Redfield, Margaret M.; Lewis, Gregory; Semigran, Marc J.; Anstrom, Kevin J.; Hernandez, Adrian F.; et al.
Abstract: Background: While abnormal left ventricular (LV) global longitudinal strain (GLS) has been described in patients with heart failure with preserved ejection fraction (HFpEF), its prevalence and clinical significance are poorly understood. Methods and results: Patients enrolled in the RELAX trial of sildenafil in HFpEF (LV ejection fraction ≥50%) in whom two‐dimensional, speckle‐tracking LV GLS was possible ( n = 187) were analysed. The distribution of LV GLS and its associations with clinical characteristics, LV structure and function, biomarkers, exercise capacity and quality of life were assessed. Baseline median LV GLS was −14.6% (25th and 75th percentile, −17.0% and −11.9%, respectively) and abnormal (≥ − 16%) in 122/187 (65%) patients. Patients in the tertile with the best LV GLS had lower N ‐terminal pro‐brain natriuretic peptide (NT‐proBNP) [median 505 pg/mL (161, 1065) vs. 875 pg/mL (488, 1802), P = 0.008) and lower collagen III N ‐terminal propeptide (PIIINP) levels [median 6.7 µg/L (5.1, 8.1) vs. 8.1 µg/L (6.5, 10.5), P = 0.001] compared with the tertile with the worst LV GLS. There was also a modest linear relationship with LV GLS and log‐transformed NT‐proBNP and PIIINP ( r = 0.29, P < 0.001 and r = 0.19, P = 0.009, respectively). We observed no linear association of LV GLS with Minnesota Living with Heart Failure scores, 6‐min walk distance, peak oxygen consumption, or expiratory minute ventilation/carbon dioxide excretion slope. Conclusions: Impaired LV GLS is common among HFpEF patients, indicating the presence of covert systolic dysfunction despite normal LV ejection fraction. Impaired LV GLS was associated with biomarkers of wall stress and collagen synthesis and diastolic dysfunction but not with quality of life or exercise capacity, suggesting other processes may be more responsible for these aspects of the HFpEF syndrome.